2021
DOI: 10.3390/life11080829
|View full text |Cite
|
Sign up to set email alerts
|

Space Radiation Protection Countermeasures in Microgravity and Planetary Exploration

Abstract: Background: Space radiation is one of the principal environmental factors limiting the human tolerance for space travel, and therefore a primary risk in need of mitigation strategies to enable crewed exploration of the solar system. Methods: We summarize the current state of knowledge regarding potential means to reduce the biological effects of space radiation. New countermeasure strategies for exploration-class missions are proposed, based on recent advances in nutrition, pharmacologic, and immune science. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 162 publications
(375 reference statements)
0
13
0
Order By: Relevance
“…There is an urgent need for the sustainable production of fresh food with distinctive, original flavors to increase appetite. During long-term space missions, enabling a self-sufficient lifestyle through the use of a nature-based regenerative life support system will help astronauts better adapt to the adverse conditions of the space environment [ 195 , 196 ]. This landscape-based approach to space habitat design helps engender a sense of place attachment from biophilia; that is, the human instinctual attachment to life-like features found in nature.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need for the sustainable production of fresh food with distinctive, original flavors to increase appetite. During long-term space missions, enabling a self-sufficient lifestyle through the use of a nature-based regenerative life support system will help astronauts better adapt to the adverse conditions of the space environment [ 195 , 196 ]. This landscape-based approach to space habitat design helps engender a sense of place attachment from biophilia; that is, the human instinctual attachment to life-like features found in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Biological countermeasures could also be utilized to protect against the ill-effects of ISR-induced oxidative stress. In 2021, Montesinos et al discussed the role of these countermeasures, which will also be summarized here [164]. Several studies have found that dietary measure and supplementation is likely to have a protective effect in astronauts.…”
Section: Countermeasuresmentioning
confidence: 99%
“…To date, the use of these agents thus far in controlled clinical scenarios, where radiation exposure can be controlled and quantitated, does not reflect the unpredictable radiation environment in space. Timing the administration of these agents would therefore be much harder in astronauts [164]. Immunomodulation-based agents include prospective DNA-and RNA-based anti-radiation vaccines in addition to anti-radiation antidotes.…”
Section: Countermeasuresmentioning
confidence: 99%
See 1 more Smart Citation
“… Spaceflight hazard Clinical conditions Management strategies Possible medications References Space radiation Degenerative diseases (e.g. cardiovascular diseases and cataracts) Radiation shielding, radiation & health monitoring Antioxidants ⁎ ( Fang et al, 2002 ; Gómez et al, 2021 ) Cancer Radiation shielding, radiation & health monitoring Antioxidants ⁎ ( Gómez et al, 2021 ; Montesinos et al, 2021 ) Changes in the central nervous system Radiation shielding, radiation & health monitoring Antioxidants ⁎ ( Cucinotta et al, 2014 ; Gómez et al, 2021 ) Isolation and confinement Behavioural changes Gardening and journaling Antipsychotics (aripiprazole and ziprasidone), anxiolytics (diazepam and lorazepam) ( Friedman and Bui, 2017 ; Odeh and Guy, 2017 ) Sleep problems Light technologies, actigraphy Hypnotic drugs (zolpidem, zaleplon), melatonin ( Friedman and Bui, 2017 ; Zivi et al, 2020 ) Fatigue 10-min self-test of vigilance and attention ( Basner et al, 2011 ) Decline in mood Journaling, virtual reality sessions Antidepressants (sertraline and venlafaxine) ( Friedman and Bui, 2017 ; Lyons et al, 2020 ) Gravity fields Muscle atrophy Aerobic and resistive exercise, software-generated workout partners ( Feltz et al, 2016 ; Gao and Chilibeck, 2020 ) Bone loss Aerobic and resistive exercise, software-generated workout partners Bisphosphonate alendronate, supplements of calcium, vitamin D an...…”
Section: Spaceflight Hazards and Medical Problemsmentioning
confidence: 99%